Enhancing Vendor Selection Integrity: Integrating Fraud Heptagon Theory Framework in the Context of Fraud Prevention - Bagaskara, Fadilah Fajar; Tumanggor, Dian Valentina; Hasan, Abdullah Abdurahman (Association of Certified Fraud Examiners Indonesia Chapter, 2025)
This study examines how financial pressure, rationalization, opportunity, arrogance, competence, culture, and religiosity influence fraudulent behavior in vendor selection processes using Fraud Heptagon Theory, making it suitable for analyzing potential fraud in Indonesia, where culture and religion are emphasized. Interviews with procurement committee members reveal that sufficient income and strong governance practices can mitigate fraud. However, rationalization, perceived opportunities, and arrogance increase fraud risk. Competence alone does not significantly impact fraud, but it can when combined with ethical training. A strong ethical culture and high religiosity are associated with lower fraud propensity. The findings suggest that aligning incentives, enhancing ethical training, implementing robust internal controls, fostering an ethical culture, and integrating religious values can reduce fraud risks. The implication of this study is to gain a deeper interpretation of the interplay of these factors preventing fraud and maintaining integrity in vendor selection.